Strategic management competitiveness & globalization : concepts and cases - Hitt, Michael A.; Ireland, R. Duane; Hoskisson, Robert E.; Harrison, Jeffrey S. (Boston, MA Cengage Learning, 2024)
Written by prominent management scholars and award-winning instructors, Hitt/Ireland/Hoskisson/Harrison's STRATEGIC MANAGEMENT: COMPETITIVENESS AND GLOBALIZATION, 14E provides an intellectually rich, yet practical, analysis of strategic management with updates, new research citations and twenty new cases.
Part 1. Strategic Management Inputs: 1. Strategic Management and Strategic Competitiveness -- 2. The External Environment: Opportunities, Threats, Industry Competition, and Competitor Analysis -- 3. The Internal Organization: Resources, Capabilities, Core Competencies, and Competitive Advantages.

Part 2. Strategic Actions: Strategy Formulation -- 4. Business-Level Strategy -- 5. Competitive Rivalry and Competitive Dynamics -- 6. Corporate-Level Strategy -- 7. Merger and Acquisition Strategies and Restructuring -- 8. International Strategy -- 9. Cooperative Strategy.

Part 3. Strategic Actions: Strategy Implementation -- 10. Corporate Governance -- 11. Organizational Structure and Controls -- 12. Strategic Leadership -- 13. Strategic Entrepreneurship.

Part 4. Case Studies: Preparing an Effective Case Analysis: Case 1. The Rise and Demise of Airbus A380 -- Case 2. Air France–Klm: A Strategy for the European Skies -- Case 3. Ant Group Backed Mybank: People, Planet, Profit in Rural China -- Case 4. Aventiv Technologies: Answering the Call for Change? -- Case 5. Blue Apron: Has the Supply Chain Disrupter Been Disrupted? -- Case 6. Gap, Inc. -- Case 7. Haier: Organizing to Build a Smart Ecosystem Brand -- Case 8. The Hershey Company: Broken Pledge to Stop Using Child Labour -- Case 9. Hilton Worldwide Holdings Inc. -- Case 10. Jio and Facebook: Adding Value Through an Alliance -- Case 11. Marriott International: Hospitality’s Uncertain Future -- Case 12. Meta: Facebook’s Pivot to the Metaverse – A Path to Dystopia or Blue Ocean Utopia? -- Case 13. Streaming the Future: Netflix’s Global Expansion -- Case 14. NIO: Battling Tesla with Battery as a Service -- Case 15. Pacari Chocolate: Building a Brand that Brings Joy from Tree to Bar -- Case 16. Developing a Sustainable Ecosystem Community: The Port of Antwerp -- Case 17. Re:Build Manufacturing—Reimagining the Conglomerate -- Case 18. Uber: The Turbulent Rise of “Everyone’s Private Driver” -- Case 19. Digital Transformation at The Washington Post: Innovating for the Next Generation -- Case 20. Driving Waymo’s Fully Autonomous Future -- Case 21. Wellington Brewery: Growth Decision in a Crowded Beer Market -- Case 22. WeWork: But Does the Corporate Governance Work?
Previously published: Mason, Ohio : South-Western Cengage Learning, c2013.
Includes bibliographical references and indexes.
Keywords: Strategic planning; Industrial management; Competition; Strategic planning -- Case studies; Competition -- Case studies